MECHANISMS FOR IMPLEMENTING INVESTMENT POLICY IN THE CONTEXT OF WAR AND POST-WAR ECONOMIC RECONSTRUCTION OF THE REGION: STRATEGIC PRIORITIES AND INSTITUTIONAL INSTRUMENTS - ZAKHARCHUK, Nataliya; HAVLOVSKA, Nataliia; RUDNICHENKO, Yevhenii; VOZNIUK, Yana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the legislative framework regulating investment activity in Ukraine. The main normative acts include the Tax and Customs Codes of Ukraine, as well as the laws "On Investment Activity," "On the Regime of Foreign Investment," "On Public-Private Partnership," among others. These acts provide legal guarantees, tax preferences, protection of investors’ rights, regulation of foreign exchange operations, and the implementation of projects within the framework of state support. The current state of investment activity in Ukraine is analyzed, particularly the investment attractiveness index, the volumes of foreign direct investment (FDI), and enterprises’ capital expenditures. It has been established that although the overall rating of the investment attractiveness index remains at a relatively low level—specifically, 2.49 out of 5 in 2024—it demonstrates a positive trend even under wartime conditions. The analysis of FDI in Ukraine for the period 2002–2024 revealed sharp fluctuations in investment flows during crisis years (2009, 2014, and 2022), as well as partial recovery in 2023. At the same time, trends in the structure of enterprises capital investments were identified: the largest volumes of investments are directed towards tangible assets (machinery, equipment, buildings), and there is a growing share of investments in intangible assets, particularly in software and intellectual property. Based on official statistical data, the article traces both the key trends in the growth and decline of investments and the factors that determine them. The main factors influencing the investment climate have been identified: on the one hand, there are positive expectations related to European integration and infrastructure reconstruction; on the other hand, there are risks associated with war, corruption, and political instability. The article presents the directions and mechanisms for implementing investment policy, which are structured into five key areas: institutional support, infrastructure recovery, financial incentives, security guarantees, and international integration. For each area, objectives have been formulated and specific implementation mechanisms proposed, including public-private partnerships, investment incentives, concessional lending, investment insurance, digital monitoring, participation in international programs, among others.